Molecular analysis of Sonic Hedgehog (SHH) in the etiology of nonsyndromic cleft lip and palate in Chilean case-parent trios - Rincón-R., Ramiro J.; Suazo, José; Blanco-C., Rafael (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: nonsyndromic cleft lip and palate (NSCLP) is one of the most common congenital malformations not only in Chile but also worldwide. It has a multifactorial inheritance pattern with interaction of several genes and the environment. Several experimental studies have proven the participation of Sonic hedgedhog (Shh) in the migration process of cells from the neural crest, in the epithelium-mesenchyme transformation, and in the formation of middle craniofacial structures during embryo development; an association between Shh variants and NSCLP is probable. Methods: the goal of this study was to evaluate both exonic and intronic regions adjacent to Shh, in a sample of 150 case-parent trios in order to find possible associations with NSCLP. The PCR-RFLP method was used to determine the presence of heteroduplex. Afterwards, the Conformation Sensitive Gel Electrophoresis (CSGE) technique was used to visualize DNA distortion at the heteroduplexes. As an alternative method, a single-nucleotide polymorphism (SNP) analysis was performed in order to determine NSCLP-Shh associations, by means of these SNPs: rs1233555 and rs1233556, located at the first Shh intron. Results: no heteroduplexes were found in any of the analyzed Shh segments in 150 trios; SNP analysis did not show associations between Shh and NSCLP either. Conclusions: this lack of association may be due to the fact that SNP distribution frequency among Chilean population is different to that of reference populations, or because the number of SNPs analyzed was not sufficient, or even because this study did not include other Shh regions.